2004
DOI: 10.1016/j.bbamem.2004.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Lipids in membrane protein structures

Abstract: This review describes the recent knowledge about tightly bound lipids in membrane protein structures and deduces general principles of the binding interactions. Bound lipids are grouped in annular, nonannular, and integral protein lipids. The importance of lipid binding for vertical positioning and tight integration of proteins in the membrane, for assembly and stabilization of oligomeric and multisubunit complexes, for supercomplexes, as well as their functional roles are pointed out. Lipid binding is stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
353
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(366 citation statements)
references
References 102 publications
8
353
0
5
Order By: Relevance
“…7–9). Lipids are known to play important roles in membrane enzyme complexes 34,35 and can mediate transient multimerization of membrane proteins 36 . A recent cryo-EM structure showed that lipids are involved in the assembly of the heterotetrameric γ-secretase 37 .…”
Section: Introductionmentioning
confidence: 99%
“…7–9). Lipids are known to play important roles in membrane enzyme complexes 34,35 and can mediate transient multimerization of membrane proteins 36 . A recent cryo-EM structure showed that lipids are involved in the assembly of the heterotetrameric γ-secretase 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Since a significant portion of integral membrane proteins remains in contact with the membrane lipids, 1 the structure and function of membrane proteins often depend on their interactions with the surrounding lipids. 2 The lipid composition of cells that make up the nervous system is unique and has been correlated with increased complexity in the organization of the nervous system during evolution. 3 The organization and dynamics of cellular membranes in the nervous system play a crucial role in the function of neuronal membrane receptors.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study analyzed the binding specificity of the phosphodiester group using 30 unique, ordered lipids seen in x-ray structures [5]. These lipids had been co-purified with the protein, indicating that they are strongly and specifically bound.…”
Section: Lipid-protein Interactionsmentioning
confidence: 99%
“…These lipids have typically originated from the native membrane and have co-purified with the protein. Analysis of such tightly bound lipids has provided insight into the specific binding of lipids to membrane proteins [5].…”
Section: Introductionmentioning
confidence: 99%